2013
DOI: 10.1016/j.cam.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Parameter range reduction for ODE models using monotonic discretizations

Abstract: This paper analyzes the effectiveness of various monotonic discretizations of an ODE in a parameter range reduction algorithm. Several properties of discretizations are given, and five classes of discretizations are defined for various step numbers s. The range reduction algorithm that employs these discretizations is described. Using both analytical results based on the prototypical model x ′ = λx, and empirical results based on two more complicated models, it is shown that one particular class of discretizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…We were motivated in particular by ODE parameter identification schemes based on monotonic discretizations [20,19]. Such schemes make use of the fact that data points lie in some known interval.…”
Section: Discussion and Further Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We were motivated in particular by ODE parameter identification schemes based on monotonic discretizations [20,19]. Such schemes make use of the fact that data points lie in some known interval.…”
Section: Discussion and Further Workmentioning
confidence: 99%
“…In some applications, it is necessary to obtain an upper and lower estimate at any given time, requiring two continuous representations: one bounding the data above and the other below. We are motivated in particular by the need for continuous upper and lower bounds of discrete data for use in a parameter range reduction algorithm for ordinary differential equation models [20,19]. Parameter estimation in this context is typically accomplished by selecting a set of initial parameter values, numerically integrating the model equations and comparing the result to the time series data.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm will make use of a specific family of linear multistep discretizations. In [14], it was shown that the best discretization formulae for parameter range reduction were called A1OUT discretizations, whose form is…”
Section: Discretizationsmentioning
confidence: 99%
“…This paper presents an improvement on a parameter range reduction method first introduced in [13,14]. The algorithm discretizes the model equations and uses these discretizations to quickly prune regions of parameter space that are deemed to be inconsistent with the data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation